A people's history of baseball - Nathanson, Mitchell, 1966-; ebrary, Inc. (Urbana : University of Illinois Press, 2012)
Probes the other side of baseball history--episodes not involving equality, patriotism, heroism, and virtuous capitalism, but power--how it is obtained, how it perpetuates itself, and how it affects the game.
Includes bibliographical references (p. [261]-269) and index.
Electronic reproduction.
Keywords: Baseball -- United States -- History; Baseball -- Social aspects -- United States -- History; Electronic books